Genital tuberculosis in females - Grace, G. Angeline (Indian J Med Res, 2017)
The morbidity and mortality due to tuberculosis (TB) is high worldwide, and the burden of disease among women is significant, especially in developing countries. Mycobacterium tuberculosis bacilli reach the genital tract primarily by haematogenous spread and dissemination from foci outside the genitalia with lungs as the common primary focus. Genital TB in females is a chronic disease with low-grade symptoms. The fallopian tubes are affected in almost all cases of genital TB, and along with endometrial involvement, it causes infertility in patients. Many women present with atypical symptoms which mimic other gynaecological conditions. A combination of investigations is needed to establish the diagnosis of female genital TB (FGTB). Multidrug anti-TB treatment is the mainstay of management and surgery may be required in advanced cases. Conception rates are low among infertile women with genital TB even after multidrug therapy for TB, and the risk of complications such as ectopic pregnancy and miscarriage is high. More research is needed on the changing trends in the prevalence and on the appropriate methods for diagnosis of FGTB.